PERLINDUNGAN HUKUM BAGI PEMILIK KAPAL TERKAIT TIDAK DIPENUHINYA KEWAJIBAN BAYAR OLEH PENCARTER DALAM PERJANJIAN CARTER KAPAL LAUT MENURUT WAKTU - Febbyanti Rahmadian; Felicitas Sri Marniati; Irhamsah, Irhamsah (Journal of Innovation Research and Knowledge, 2025)
A time-based ship charter agreement, as a reciprocal contract, obligates the shipowner to provide the vessel to the charterer and requires the charterer to pay the charter fee to the shipowner. This study aims to examine the legal consequences arising from the charterer's failure to fulfill the payment obligation to the shipowner, using an analysis based on the theory of legal consequences as presented by R. Soeroso. Additionally, this study seeks to explore the legal protection available to the shipowner in relation to the charterer's non-fulfillment of payment obligations, applying the legal protection theory proposed by Satjipto Rahardjo The method used in this research is a type of normative juridical research, namely literature law research or secondary data with sources of primary, secondary, and tertiary legal materials. The research approaches used are legislation, analysis, case, and conceptual approaches. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, literature, books, journals and other sources of legal materials. For legal material analysis techniques, it is carried out by grammatical, systematic legal interpretation and legal construction methods. From the results of the study, it can be obtained that the legal consequences of non-implementation of the payment obligation by the charterer are in the form of fulfillment of the agreement, fulfillment of the agreement with compensation for damages, compensation for damages, cancellation of mutual agreements, or cancellation with compensation for damages. The legal protection provided to ship owners is by the rules of material law and formal law in laws and regulations.